Patient experience of post-extraction pain management - Truitt, Anjali R.; Asche, Stephen E.; Ziegenfuss, Jeanette Y.; Mitchell, Shannon G.; Gryczynski, Jan; Kane, Sheryl M.; Worley, Donald C.; Rindal, D. Brad (Frontiers in Dental Medicine, 2022)
Introduction Few studies have assessed the impact of clinical decision support, with or without patient education, on patient-reported outcomes in dentistry. This cross-sectional survey was conducted to understand patients' experience with shared decision-making and pain management associated with a tooth extraction. Methods We administered a phone survey to 981 adult patients within a week of having a tooth extraction. The tooth extraction was performed at a large regional dental practice by a dentist participating in a randomized controlled trial of a clinical decision support system to reduce reliance on opioids for tooth extraction-related pain management. The survey compared respondents' answers by study arm: standard practice (SP) or clinical decision support with (CDS-E) or without patient education (CDS). Results Of respondents (n = 492, response rate: 52%), 91% reported that their dental provider talked about what to expect for pain in the days following the extraction, 92% stated that their dental provider talked about how to treat post-extraction pain, and 74% expressed they were confident in their ability to manage post-extraction pain at the end of the extraction visit. We found no statistically significant differences in patient responses across study arms for average pain in the 3 days following the extraction (p = 0.65, CDS vs. SP; p = 0.41, CDS-E vs. SP) or in shared decision-making (p = 0.38, CDS vs. SP; p = 0.70, CDS-E vs. SP). Conclusion Most patients reported adequate pain management and shared decision-making about pain management related to their tooth extraction. Further research will assess differences in analgesic recommendations across study arms.